A cross sectional study of prevalence of depression among patients with cerebrovascular accident - A., Chamelee; Selvamani, Iniyan; N., Venkatraman; Nambi, Shanthi; Chandraleka, G. S. (International Journal of Research in Medical Sciences, 2019)
Background: Depression is one of the most common neuropsychiatric condition in patients with stroke. Early identification of depression for stroke patients can improve the outcome leading to better quality of life. Prevalence and determinants of post stroke depression are highly variable and there is paucity of data in Indian literature. Methods: This cross-sectional study was conducted at neurology department of Saveetha Medical College, Chennai. All patients with history of stroke within past one month attending neurology department who fulfilled the inclusion criteria were taken up for the study after getting consent. Neurological examination and CT brain findings were noted with the site of lesion. All patients were evaluated for depression using ICD 10 criteria. MADRS score was used to assess the severity of depression. Chi square was used for statistical analysis. Results: The mean age of subjects in the study was 56.54±10.82 years. The prevalence of depression among patients with stroke in our study was 75.8%. Among classifying those with depression based on severity using MADRS score, 35% had mild depression and 65% had moderate depression. There was no severe depression in our sample. There was no statistically significant difference between prevalence of depression based on side of lesion. Conclusions: In this study the prevalence of depression among patients with cerebrovascular accident was found to be 75.8%. From this study we learn that the prevalence of depression in patients with stroke is high and this shows that regular screening of patients with stroke for depression might help in earlier detection and management of depression.